Postoperative Clostridium difficile infection with PCR ribotype 078 strain identified at necropsy in five Thoroughbred racehorses. (21st December 2013) - Niwa, H.; Kato, H.; Hobo, S.; Kinoshita, Y.; Ueno, T.; Katayama, Y.; Hariu, K.; Oku, K.; Senoh, M.; Kuroda, T.; Nakai, K.
Abstract : Clostridium difficile is an important cause of acute enterocolitis in horses. We describe five cases of C difficile infection occurring postoperatively in Thoroughbred racehorses. Following diarrhoea or colic accompanied by a marked increase in packed cell volume (to ≥60 per cent) and leucopenia (≤4000 cells/μl) within two to four days after surgery in all five horses, four of them died or were euthanased because of colitis or severe diarrhoea. In these four horses, necrotising entero‐typhlo‐colitis was revealed by postmortem examination, and C difficile was recovered from the contents of the small and/or large intestine. The remaining horse was euthanased because of marked decline in general condition and the presence of a lung abscess, from which C difficile was isolated. The horse had had severe postoperative diarrhoea before the onset of respiratory disorder; laboratory tests for C difficile were not performed on the faeces. All C difficile isolates were toxin‐A‐positive, toxin‐B‐positive and actin‐specific ADP‐ribosyltransferase (CDT)‐positive. The isolates were indistinguishable by pulsed field gel electrophoresis analysis, PCR ribotyping, and slpA sequence typing, and the slpA sequences and PCR ribotype patterns were identical to those of known PCR type 078. This case sequence might have been healthcare‐associated infection, although there was about a four‐month interval between each disease onset.